Structure of the vertical and horizontal system neurons of the lobula plate in Drosophila. - Scott, E.K.; Raabe, T.; Luo, L. (Journal of Comparative Neurology, 2002)
The lobula plate in the optic lobe of the fly brain is a high-order processing center for visual information. Within the lobula plate lie a small number of giant neurons that are responsible for the detection of wide field visual motion. Although the structure and motion sensitivity of these cells have been extensively described in large flies, the system has not been described systematically in Drosophila. Here, we use the mosaic analysis with a repressible cell marker (MARCM) system to analyze a subset of these cells, the horizontal and vertical systems. Our results suggest that the Drosophila horizontal system is similar to those described in larger flies, with three neurons fanning their dendrites over the lobula plate. We found that there are six neurons in the Drosophila vertical system, a figure that compares with 9-11 neurons in large flies. Even so, the Drosophila vertical system closely resembles the systems of larger flies, with each neuron in Drosophila having an approximate counterpart in large flies. This anatomical similarity implies that the inputs to the vertical system are similarly organized in these various fly species, and that it is likely that the Drosophila neurons respond to motions similar to those sensed by their specific structural counterparts in large flies. Additionally, the similar appearance of vertical system cells in multiple cell clones demonstrates that they share a common developmental lineage. Access to these cells in Drosophila should allow for the use of genetic tools in future studies of horizontal and vertical system function.